Place, peers, and the teenage years: Long-run neighborhood effects in Australia - Deutscher, Nathan (American Economic Journal: Applied Economics)
I use variation in the age at which children move to show that where an Australian child grows up has a causal effect on their adult income, education, marriage, and fertility. In doing so, I replicate the findings of Chetty and Hendren (2018a) in a country with less inequality, more social mobility, and different institutions. Across all outcomes, place typically matters most during the teenage years. Finally, I provide suggestive evidence of peer effects using cross-cohort variation in the peers of permanent postcode residents: those born into a richer cohort for their postcode tend to end up with higher incomes themselves. - Reproduced
Keywords: Australia, Teenagers